2015
DOI: 10.1038/bmt.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment syndrome: double-edged sword of hematopoietic cell transplants

Abstract: Engraftment syndrome (ES) after hematopoietic cell transplantation (HCT) is increasingly diagnosed. Common features include fever, pulmonary vascular leak, rash and organ dysfunction. Different diagnostic criteria likely account for the wide (7-90%) range of reported incidences. ES typically occurs within 4 days of granulocyte recovery although a recently described seemingly similar syndrome occurs 41 week before granulocyte recovery after umbilical cord blood cell transplants. Although the clinical manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 45 publications
2
132
0
3
Order By: Relevance
“…It was first described by Lee et al in a retrospective analysis of 248 patients with cancer undergoing auto-HSCT [29,30]. ES has also been described after allogeneic HSCT, but it has been more frequently reported following auto-HSCT [28,31,32]. The risk factors of ES include: MM and lymphoma as the underlying illnesses, previously administered chemotherapy and radiotherapy, faster engraftment and infusion of higher number of stem cells [14,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was first described by Lee et al in a retrospective analysis of 248 patients with cancer undergoing auto-HSCT [29,30]. ES has also been described after allogeneic HSCT, but it has been more frequently reported following auto-HSCT [28,31,32]. The risk factors of ES include: MM and lymphoma as the underlying illnesses, previously administered chemotherapy and radiotherapy, faster engraftment and infusion of higher number of stem cells [14,28].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of ES resemble those of acute GVHD and they include: fever, skin rash, hepatic and renal dysfunction, transient encephalopathy, capillary leak syndrome and death [28,29,31,33]. ES has to be differentiated from autologous GVHD, infections as well as drug toxicity and radiation induced tissue damage [31]. ES is typically self-limited and it usually responds to corticosteroids, supportive care and other immunosuppressive…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Vascular leak, organ dysfunction and constitutional signs such as fever are secondary to activated leucocytes and pro-inflammatory cytokines during engraftment process. 59 It was reported that IL-1, TNFalpha, interferon gamma, IL-2 receptor-alpha and TNF-receptor levels increased in ES as in acute International Journal of Hematology and Oncology GVHD. 54 Soluble thrombomodulin and plasminogen activator type I, CRP increase and complement activation are changes detected in ES.…”
Section: Engraftment Syndromementioning
confidence: 99%